Wavelet analysis of multiparticle correlations - Fedorišin, J. (Array, 2008)
Summary: Applicability of continuous wavelet analysis to pseudorapidity and azimuthal distributions of secondary particles produced in Au + Au collisions at Ö{sNN}=200 GeV at Relativistic Heavy Ion Collider is studied. After corrections for boundary effects, the wavelet spectra are presented on different scales. We present a discussion whether the multi-particle collective flows produced by different physical mechanisms can be detected through extremes in the wavelet spectra or corresponding scalograms, and what additional information concerning correlation structure of events can be extracted by this analysis